2012
DOI: 10.1590/s1415-43662012000700008
|View full text |Cite
|
Sign up to set email alerts
|

Sorção de potássio em amostras de solo submetidas à aplicação de vinhaça

Abstract: R ESU M ONo processo de produção do etanol a vinhaça é um subproduto gerado em grande escala, em média, na razão de aproximadamente 13 L de vinhaça por litro de álcool destilado. Este volume produzido representa um problema no acondicionamento e nos processos de tratamento deste efluente que, na maioria das vezes, é lançado no solo por fertirrigação. Tendo em vista os altos teores de nutrientes, com destaque para o potássio e o alto teor de matéria orgânica, a disposição da vinhaça no solo necessita de estudos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
2
6
0
8
Order By: Relevance
“…The results of the analysis of vinasse are presented in Table IV and corroborate the claim of Nicochelli et al (2012), according to which vinasse has an acidic character (pH < 4.0) and high levels of K.…”
Section: Soil Mineralogysupporting
confidence: 78%
See 2 more Smart Citations
“…The results of the analysis of vinasse are presented in Table IV and corroborate the claim of Nicochelli et al (2012), according to which vinasse has an acidic character (pH < 4.0) and high levels of K.…”
Section: Soil Mineralogysupporting
confidence: 78%
“…Before the equilibrium batch tests, the test of K sorption kinetics was performed according to Nicochelli et al (2012). For this study, the established times were 0, 2, 6, 12, 18, 24, 36 and 48 h. The samples of the kinetic test remained at ambient temperature, with the same proportion of equilibrium batch tests (1:4 ratio) and concentration, only and intermediate, of 213.87 mg.L -1 of K from the diluted vinasse solution, to identify the ideal stabilization time for the adsorption of the solute in the soil.…”
Section: Sorption Kinetics and Equilibrium Batch Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os métodos empregados no estudo de sorção e na avaliação da mobilidade de solutos no solo, segundo Nicochelli et al (2012), Chaves e Tito (2011), Castro et al (2010), Oliveira et al (2010a;2010b) As isotermas de sorção são curvas que representam a concentração de espécie química sorvida pela sua concentração não sorvida a uma temperatura constante, podendo ser ajustado modelos matemáticos utilizados para quantificar a capacidade de sorção de um elemento pelo solo. As equações de Langmuir e Freundlich têm sido utilizadas com frequência para descrever a sorção de diferentes elementos químicos pela fase coloidal do solo (SODRÉ et al, 2001).…”
unclassified
“…Silva et al (2012) have observed that the addition of vinasse in clayey soil has increased the sorption capacity of potassium and, to a lesser intensity, sodium. Thus the increased retention of these ions to the soil can encourage competition between them and herbicidal molecules for adsorption sites available on the ground -this process tends to be enhanced in acid solutions due to competition between cations and ions H + (Nicochelli et al, 2012). Spark & Swift (2002) have found that fulvic acid applied to the soil competes for sorption sites between 2,4-Dichlorophenoxyacetic acid and the soluble organic fraction, providing the herbicide in the soil solution.…”
Section: Resultsmentioning
confidence: 99%